PENGARUH KONSENTRASI BAYCLIN PADA PENCUCIAN II DAN BAP PADA MEDIA MS TERHADAP PERTUMBUHAN EKSPLAN TANAMAN PISANG KLUTUK (Musa paradisiaca. L) SECARA IN VITRO - Zulkifli Zulkifli; Putri Lukmana Sari (DINAMIKA PERTANIAN, 2017)
This research aims to examie the effect of bayclin concentration on washing II and BAP in MS media on eksplan growth of klutuk banana in vitro and was conducted at the Tissue Culture Laboratory Lempes Pekanbaru from April to August 2016. The research used a completely randomized design (CRD) with 3 factorials and 3 replications. The first factor was the concentration of washing eksplan bayclin on phase II which consisted of four levels: K0 (concentration of 0%), K1 (concentration of 10%), K2 (concentration of 20%), and K3 (concentration of 30%). The second factor was the concentration of BAP contained on media MS consisted of four levels: T0 (BAP concentration 0 mg/liter), T1 (BAP concentration of 0.1 mg/liter), T2 (BAP concentration of 1.0 mg/liter) and T3 (BAP concentration of 10.0 mg/liter). The parameters observed were percentage of explants contaminated, age appears buds, the number of shoots/explant, length of shoots/explant, number of roots/explant (root), root length/explant and percentage of explant life. The results showed that effect of concentration on the washing bayclin II and BAP in MS Media on growth eksplan of klutuk banana in-vitro was the best treatment K2T2 with 33.33% of explants contaminated, age of appears buds 2,67 weeks after planting, the number of shoots 2,67/explant, length of shoots 5,50 cm/explant, number of roots 2.67/explant, root length 12,08 cm/explant and 58.33% of explants life.